Gene dosage and protein valency impact phase separation and fungal cell fate. - Collin Ganser; Peiling He; Corey Frazer; Damian J Krysan; Richard J Bennett (PLoS Genetics)
Cell fate decisions in eukaryotes are regulated by interconnected networks of transcription factors (TFs) that drive heritable changes in identity. However, much is unknown about how TFs act together to control cell fate, despite links to cellular dysfunction and disease when TF function is aberrant. Here, we addressed the interplay between TFs that control heritable switching in the diploid fungal pathogen Candida albicans. This species can propagate in two distinct cell states, white and opaque, with epigenetic transitions between states regulated by a core network of eight TFs plus >100 auxiliary TFs. The role of these TFs was dissected using simple and complex haploinsufficiency (CHI) analyses to examine the impact of gene dosage on cell fate. Among single heterozygotes, loss of one allele of WOR1 had the greatest impact on white-opaque switching, consistent with its role as the master opaque regulator, while CHI analysis revealed strong genetic interactions between other core TFs including WOR3 and WOR4. Wor1 function was also highly sensitive to its interaction valency, a measure of the number of inter-molecular interactions it can undergo. Engineered strains with increased Wor1 valency, either via the addition of extra prion-like domains (PrLDs) or by forced dimerization, increased switching frequencies by up to two orders of magnitude. Increasing Wor1 valency increased its propensity to form phase-separated condensates both in vitro and in mammalian cells. Together, these experiments establish that changes to TF gene dosage and TF valency can alter cell fate determination, with these changes linked to the propensity of TFs to undergo condensate formation.